The insertion I/deletion D polymorphism of angiotensin converting enzyme (ACE) gene in type II diabetic - Sapkota, R; Dasgupta, R; Das, Banashree; Rai, Luna (Recent Research in Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Purpose: The causes of T2DM are mainly unknown, but they arise from interplay between several genetic and environmental factors. The I/D allele of the ACE gene has been studied in Indian population in relation to T2DM with contradictory results. Hence the present study was aimed to investigate whether the I/D polymorphism of ACE gene increase the susceptibility to T2DM. Material and methods: ACE gene was genotyped in 119 patients, 59 (aged matched and sex no matched) patients and 50 (age matched and no sex matched) controls. Results: The Hardy Weinberg equilibrium was tested for the entire group. The χ2 (chi-square) test with Fisher’s correction was used to compare the genotype and allele frequency in the cases, on the one hand, and the controls, on the other . The II genotype occurred more frequently in North Indian population with type II diabetes mellitus patient (30%) than in the control (12%). The genotypic and allele frequencies differed significantly in case from control subjects (p<0.05). Conclusion: From the present data it was observed that in T2DM patient genotypic and allele frequencies were significantly deviated from Hardy-Weinberg equilibrium (p<0.05).The involvement of II genotype occurred more frequently among the case subjects.